2016
DOI: 10.3390/rs8100836
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of Three Satellite Precipitation Products over Africa

Abstract: Abstract:We present an evaluation of daily estimates from three near real-time quasi-global Satellite Precipitation Products-Tropical Rainfall Measuring Mission (TRMM) Multi-satellite Precipitation Analysis (TMPA), Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks (PERSIANN), and Climate Prediction Center (CPC) Morphing Technique (CMORPH)-over the African continent, using the Global Precipitation Climatology Project one Degree Day (GPCP-1dd) as a reference dataset for y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…The very low bias (0.05 mm) can probably be explained by the summed effect of false alarms (overestimations) and missed events (underestimations) of daily rainfall, which tend to balance out. While both CMORPH‐BLD and PERSIANN‐CDR assimilate information from infrared (IR) and passive micro‐waves (PMW) sensors, TMPA extends its retrieval synthesis further to include information from TRMMs orbital radar, which seems to improve the quality of estimates compared to the other two products (Serrat‐Capdevila et al ., ). Overall, the validation metrics suggest that TRMM‐3B42 can be useful to reproduce the observed rainfall characteristics aggregated at coarser timescales (i.e., monthly and seasonally).…”
Section: Discussionmentioning
confidence: 99%
“…The very low bias (0.05 mm) can probably be explained by the summed effect of false alarms (overestimations) and missed events (underestimations) of daily rainfall, which tend to balance out. While both CMORPH‐BLD and PERSIANN‐CDR assimilate information from infrared (IR) and passive micro‐waves (PMW) sensors, TMPA extends its retrieval synthesis further to include information from TRMMs orbital radar, which seems to improve the quality of estimates compared to the other two products (Serrat‐Capdevila et al ., ). Overall, the validation metrics suggest that TRMM‐3B42 can be useful to reproduce the observed rainfall characteristics aggregated at coarser timescales (i.e., monthly and seasonally).…”
Section: Discussionmentioning
confidence: 99%
“…Via a multiple comparison ranking, and by taking GPCC (Global Precipitation Climatology Centre) data over entire Africa and rain-gauge observations over the Greater Horn of Africa as references, it was found that PERSIANN had the highest signal-to-noise ratio, followed by ARC v2, TMPA, CMORPH, TAMSAT and GSMaP. A similar T A B L E 1 Inventory of satellite rainfall estimates datasets listed in the literature review or used in the study (upper part of the intercomparison, taking into account a smaller number of datasets but at a finer temporal resolution (daily) was carried out by Serrat-Capdevila et al (2016). TMPA was found to have the smallest bias in Central Africa compared to the other products, underestimating daily rainfall on average by less than 10%, and PERSIANN has the smallest median errors of rainfall amounts when it correctly detects precipitation events.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, the RRI model has been utilized with GSMaP to simulate the 2008 flood event in Pakistan [20]. In the meantime, SRE products have been compared with each other and their characteristics and accuracy have also been evaluated [21][22][23]. However, evaluation among multiple SREs in terms of flood inundation reproducibility has not been done yet.…”
Section: Introductionmentioning
confidence: 99%